2018
DOI: 10.1097/pec.0000000000001403
|View full text |Cite
|
Sign up to set email alerts
|

Video Recordings to Analyze Preventable Management Errors in Pediatric Resuscitation Bay

Abstract: Objective In treating patients of different ages and diseases in the pediatric resuscitation bay, management errors are common. This study aimed to analyze the adherence to advanced trauma life support and pediatric advanced life support guidelines and identify management errors in the pediatric resuscitation bay by using video recordings. Methods Video recording of all patients admitted to the pediatric resuscitation bay at University Children's Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In our study, we use one device to analyze CC quality. We also used video recordings to asses pediatric resuscitation management and to detect errors or omissions during resuscitation because previous studies showed that it is a useful tool for this purpose 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we use one device to analyze CC quality. We also used video recordings to asses pediatric resuscitation management and to detect errors or omissions during resuscitation because previous studies showed that it is a useful tool for this purpose 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, using a method of audio‐video recording, transcribing ten highly complex operations and then identifying deviations by majority consensus of a multidisciplinary team, a mean of one deviation every 79 min during complex procedures has been reported. Similarly, using videos, a statistically significant correlation between accurate handover and adherence to guidelines was found in an advanced trauma paediatric resuscitation bay.…”
Section: Resultsmentioning
confidence: 89%
“…One study was excluded from further analysis because of low outcome and analysis scores ( Appendix S2 , supporting information). Thus, 20 studies showing good internal and external validity remained, and were used for in‐depth analysis.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, p-OHCA accounts for a further 7037 children brought to United States PEDs each year [1]. Variable adherence to resuscitation algorithms is commonly observed and can hinder optimal trauma and CPR care, thus jeopardizing patient outcome and survival [60][61][62][63][64]. In addition to the technical skills of individual rescuers, shared mental non-technical skills at the team level such as SA, collective team interaction patterns, leadership, and dynamic decision-making affect adherence to algorithms and hence the outcome of resuscitation care [22,65].…”
Section: Discussionmentioning
confidence: 99%